2013
DOI: 10.1007/s00268-013-2160-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower Reoperation Rate for Recurrence after Mesh versus Sutured Elective Repair in Small Umbilical and Epigastric Hernias. A Nationwide Register Study

Abstract: In total, 4,786 small (≤ 2 cm) elective open umbilical and epigastric hernia repairs were included. Age was median 48 years (range 18-95 years). Follow-up was 21 months (range 0-47 months). The cumulated reoperation rates for recurrence were 2.2 % for mesh reinforcement and 5.6 % for sutured repair (P = 0.001). The overall cumulated reoperation rate for sutured and mesh repairs was 4.8 %. In conclusion, reoperation rate for recurrence for small umbilical and epigastric hernias was significantly lower after mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 28 publications
2
62
1
5
Order By: Relevance
“…Suture repair or the Mayo technique for umbilical hernia closure are both associated with a recurrence rate of 10%–30% 12,13. The use of a prosthetic mesh, even for small defects, significantly reduces hernia recurrence 2,3,14. This 1-year interim analysis of the PANACEA trial shows a low 12-month recurrence rate of 2.8% (3/106).…”
Section: Discussionmentioning
confidence: 91%
“…Suture repair or the Mayo technique for umbilical hernia closure are both associated with a recurrence rate of 10%–30% 12,13. The use of a prosthetic mesh, even for small defects, significantly reduces hernia recurrence 2,3,14. This 1-year interim analysis of the PANACEA trial shows a low 12-month recurrence rate of 2.8% (3/106).…”
Section: Discussionmentioning
confidence: 91%
“…Combining data from the DVHD with data from patient files, patient questionnaires, and clinical examinations revealed that mesh repairs reduce the risk for recurrence significantly,7 even in small repairs and without increased risk of pain 10,11. Additionally, large-size data from DVHD have shown that laparoscopic intraperitoneal mesh fixation with absorbable as compared with titanium tacks is associated with an increased risk of hernia recurrence.…”
Section: Examples Of Researchmentioning
confidence: 99%
“…The nationwide studies have pointed out several areas for surgical improvement for the different types of ventral hernias to reduce risk for early and late complications and recurrence. These include the advantageous application of a sublay mesh during open repair of an incisional hernia7 and use of a mesh for open umbilical or epigastric hernia repair to reduce recurrence 10…”
Section: Examples Of Researchmentioning
confidence: 99%
“…The evidence that umbilical and epigastric hernias must be repaired using a mesh, in analogy with other hernias, is accumulating [1-7]. The use of a mesh in large hernias reduces the risk of recurrence from approximately 15-40% to 1-10% [1,4-6,8-10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results of the Hernia Umbilicalis Mesh versus Primair suture (HUMP) trial that focuses on hernias smaller than 2 centimetres will have great added value for umbilical hernias in particular [11]. Other retrospective studies suggest that for the reoperation rate due to recurrence mesh is superior in umbilical and epigastric hernias [7]. In contrast to the HUMP trial, which places the mesh in this pre-peritoneal plane, a mesh can also be placed intraperitoneally.…”
Section: Introductionmentioning
confidence: 99%